Improved project control for sustainable development of construction sector to reduce environment risks - Malik, S. (Elsevier Ltd, 2019)
This study examines how environmental concerns impact the connectivity amid formal, informal control and performance based on data gathered from different 156 construction companies. The empirical outcomes illustrate that behaviour, outcome relationship between variables and clan control affirmatively affect performance on construction projects. However, self-control is unimportantly identified with project execution. This research uncovers that in construction projects, the adequacy of managerial control varies. The results further suggest that interior environmental concerns contrarily moderate the consequence of control of cleaner merchandise enactment during projects. However, external natural hazards emphatically direct the adequacy of project control, showing noteworthy and assorted roles played by different ecological dangers in the assembly of control and project execution. The interactive empirical outcomes between formal control and external environmental hazards are significantly related to project performance(t > 2, and p < 0.05) however the controlling impact of the inner environmental hazard on project control is relatively lower (Î² = 0.338, p > 0.05). The study concluded the least significant of all controller means towards the enactment of construction projects. Results showed that for complex projects, operative control approaches should be prioritised over ineffective control methods. Â© 2019 Elsevier Ltd